(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article analyzes the stages of the development of criminal law norms in French criminal law, which establish responsibility for crimes against the freedom of a person. Freedom presupposes that people can determine their own destiny, goals and aspirations, and realize them independently according to their subjective will. That is why in all periods of historical development, people have been striving for freedom and fighting for freedom and liberty. The norms defining responsibility for crimes against the freedom of a person in the French criminal laws were analyzed, the aspects of these norms different from the norms defined in the current criminal law of the Republic of Uzbekistan were determined, and the issues of restoring the positive experiences existing in the processes of historical development and improving the current criminal law were studied.